Training China’s Early Modern Lawyers: Soochow University Law School - Conner, Alison W. (Columbia Journal of Asian Law, 1994)
Late imperial China produced neither a private, independent legal profession nor a formal program for training legal specialists! The introduction of legal and educational reforms in the closing years of the Qing dynasty (1644-1911), however, led to the establishment of schools offering courses in “law and government,” not only in the capital but also throughout the provinces. Their main purpose was to train officials for judicial and tax positions while providing an alternative to the traditional examination system. Such law and government schools soon outnumbered other new schools and attracted the most students because they offered several fields of study, the government permitted them to be established privately, and legal talent was seen as necessary for the proposed constitutional government. Consequently, according to one source, they became the core of higher education at that time.